Broadband continuous mode power amplifier with on‐board harmonic injection. Issue 9 (16th April 2019) - Mary Asha Latha, Yericharla; Rawat, Karun; Helaoui, Mohamed; Ghannouchi, Fadhel M.
Abstract : This study presents the design of a broadband continuous mode power amplifier (PA) with an active harmonic injection (HI). Since the injected harmonic signal is generated on‐board using a frequency doubler, this design has a single radio frequency input. The generated second harmonic is injected at the drain terminal of a gallium nitride high‐electron‐mobility transistor used in designing continuous class B/J PA. A design space in terms of amplitude and phase of the injected harmonic signal is analysed to obtain the loads that operate the PA in the continuous class B/J mode at the current generator reference plane. The proposed design strategy is verified by designing a prototype with a frequency doubler and a PA using 10 and 15 W gallium nitride high‐electron‐mobility transistors, respectively. The measured drain efficiency of 60.04–70.96% and output power of 40.17–42.6 dBm is obtained from 1 to 1.9 GHz. This corresponds to a broadband operation of 900 MHz with 62% fractional bandwidth. The designed HI–PA is also tested with a 20 MHz long‐term evolution signal whose corresponding adjacent channel power ratio is better than −47.76 dBc in the overall band after applying digital predistortion.